The Influence of Government Agency Support and Social Media on Sustainable Competitive Advantage is Mediated by Entrepreneurial - Sari, Ni Kadek Wahyuni Merta (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to determine the impact of support from government agencies and social media on the sustainable competitive advantage of SMEs in North Lombok Regency and to explore the role of entrepreneurial orientation as a mediator in the relationship between support from government agencies, social media and sustainable competitive advantage. The sample in this research is. SMEs in North Lombok Regency amounted to 100 respondents using a simple random sampling method. This research uses the PLS (Partial Least Squares) analysis method. The results of this research show that the variables of government agency support and social media have a significant positive effect on the variables of sustainable competitive advantage and entrepreneurial orientation. The entrepreneurial orientation variable has a significant positive effect on the sustainable competitive advantage variable. Entrepreneurial orientation and social media variables play a partial mediator role between government support and sustainable competitive advantage.